For demonstrating the identity, we'll use the method of
mathematical induction, which consists in 3
steps:
1) verify that the method works for the number
1;
2) assume that the method works for an arbitrary number,
k;
3) prove that if the method works for an arbitrary
number k, then it work for the number k+1, too.
4) after
the 3 steps were completed, then the formula works for any
number.
Now, we'll start the first
step:
1) 1^2=1*(4*1^2-1)/3 => 1=3/3=1
true.
2) 1^2 + 2^2 + ... + (2k-1)^2 = k(4k^2-1)/3 ,
true.
3) If 1^2 + 2^2 + ... + (2k-1)^2 = k(4k^2-1)/3,
then
1^2 + 2^2 + ... +(2k-1)^2 +
(2k+1)^2=(k+1)(4(k+1)^2-1)/3
Let's see if it is
true.
For the beginning, we notice that the sum from the
left contains the assumed true equality,1^2 + 2^2 + ... + (2k-1)^2=k(4k^2-1)/3. So,
we'll re-write the sum by substituting a part of it with
k(4k^2-1)/3.
k(4k^2-1)/3 + (2k+1)^2 =
(k+1)(4(k+1)^2-1)/3
4k^3-k+3(4k^2+4k+1)=(k+1)(4k^2+8k+4-1)
4k^3-k+12k^2+12k+3=4k^3+8k^2+3k+4k^2+8k+3
4k^3+12k^2+11k+3=4k^3+12k^2+11k+3
true.
4) The 3 steps were completed, so the identity is tru
for any value of n.
1^2 + 2^2 + ... + (2n-1)^2 =
n(4n^2-1)/3
No comments:
Post a Comment